Expression of cell adhesion molecules in laryngeal carcinoma – preliminary analysis - Morawski, Piotr; Kopta, Renata; Mochocki, Marcin; Brzezińska-Błaszczyk, Ewa; Lewy-Trenda, Iwona; Circle, Student Scientific; Starska, Katarzyna (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : Intercellular adhesion molecules present in immunocompetent cells as well as endothelium and tumour cells can regulate cell migration, angiogenesis, apoptosis, proliferation, and metastases in solid tumours. The aim of this study was to analyse the sICAM-1 (soluble intercellular adhesion molecule 1) and sVCAM-1 (soluble vascular cell adhesion molecule 1) expression in peripheral blood mononuclear cell (PBMC) cultures, and to find their relationships with clinicomorphological characteristics in laryngeal cancer. Materials and methods : The analysis included a group of 50 patients with verified squamous cell carcinoma of the larynx. The control group constituted 30 healthy volunteers. The pathological assessment included pTNM, stage, histological grade, and type of invasion according to the tumour front grading. The expression of adhesion molecules was assessed using the enzyme-linked immunosorbent assay (ELISA). Results: Increased expression of sICAM-1 and sVCAM-1 was an indicator of more aggressive laryngeal carcinomas. More advanced local changes evaluated on the pT feature were connected with a higher sVCAM-1 (p = 0.017), but not sICAM-1 level. The presence of lymph node metastases correlated with a higher expression of adhesion molecules (p = 0.012 and p = 0.003, for sICAM-1 and sVCAM-1, respectively). Tumours with more diffuse growth and infiltrating with small cell groups (< 15/hpf) was characterised by the highest level of adhesive proteins (p = 0.001 and p = 0.02 for sICAM and sVCAM, respectively). Moreover, lower levels of sICAM-1 and sVCAM-1 were observed more frequently in patients who lived longer than five years after treatment. Conclusions : The study indicates the importance of the sICAM and sVCAM expression as indicators of advanced changes and prognosis in patients with laryngeal carcinoma.